A Review of Gas Capture and Liquid Separation Technologies by CO2 Gas Hydrate; Energies; Vol. 16, iss. 8 - Misyura S. Ya. Sergey Yakovlevich; Strizhak P. A. Pavel Alexandrovich; Meleshkin A. V. Anton Viktorovich; Morozov V. S. Vladimir Sergeevich; Gaydukova O. S. Olga Sergeevna; Shlegel N. E. Nikita Evgenjevich; Shkola M. V. Mariya Valerjevna (2023, 2023)
Title screen